Clarifying the Methanol Synthesis Mechanism via CO2 Hydrogenation on the Cu(111) Surface: Insights from Accurate Doubly Hybrid Density Functionals - Chen, Zheng; Liu, Zhangyun; Xu, Xin (ACS catalysis, 2025)
Methanol synthesis via CO2 hydrogenation on copper-based catalysts is an emerging industrial process that has a growing importance in chemical production. Yet, the elucidation of the reaction mechanisms and the identification of active sites remain subjects of ongoing debate. Due to experimental challenges, experiments alone are insufficient to provide a complete picture of the energy landscape. Meanwhile, the proposed reaction mechanisms often rely on density functional theory calculations at the generalized gradient approximation (GGA) level, which can introduce considerable uncertainty. Here, we employ an advanced hybrid method, XYG3:GGA, that combines the doubly hybrid XYG3 functional with the periodic GGA to investigate the methanol synthesis on the Cu(111) surface. This hybrid method yields results that align well with the available energy landscape in the experiment while resolving the controversy between the experimental observation of the H2COO* intermediate and the GGA-predicted pathway from the HCOOH* intermediate. It further clarifies that the Cu(111) site makes such an insignificant contribution that it cannot be considered the active site for the methanol formation on copper catalysts. These findings highlight the importance of using more accurate methods, such as XYG3:GGA, to elucidate the reaction mechanism and identify the active site, thereby bridging the gap between the experiment and theory.